Posting strategies of CEOs of Latin American companies on LinkedIn and their impact on engagement - Saavedra, Giancarlo (2024)
This study investigates the posting strategies of CEOs of Latin American companies on LinkedIn and their impact on engagement. It examines activity levels and types of presence, and engagement rates. Based on a quantitative analysis, the results reveal that executives in this region have a significantly lower frequency of posting on LinkedIn compared to the averages recommended by experts. Regarding the type of presence, CEOs are "content creators" and mainly post their own content. The engagement analysis shows discrepancies between own and hybrid posts. Due to the originality of own content, it receives better engagement rates than hybrid posts. The findings reveal that most Latin American CEOs adopt a "passive funnel" posting strategy on LinkedIn, which is characterized by low activity and own content. It is striking that CEOs with a more passive approach tend to have higher engagement rates compared to those with a more active approach. From these findings it is clear that, although authentic content generates interaction, CEOs should take advantage of the potential of shared publications, which are characterized by fostering dialogue based on content with diverse perspectives, a particular feature of the actors and institutions of the business environment. This research assesses the potential of CEOs as institutional communicators and provides methodological guidelines for academics and professionals in charge of the publication strategies of organizations and managers in the region.